Determinants of the intention to continue using e–wallet during the covid–19 pandemic - Rahayu, Isti; Prasetyatama, Galang (Journal of Contemporary Accounting, 2021)
Information technology has grown rapidly; one of the industry’s products in the trend in Indonesia is e-wallet, such as OVO and DANA. This research study aims to find out the empirical evidences regarding the perceived risks, reputations, service features, and promotions on the intention to use e-wallet with experiences as the moderating variable. The data used in this research is primary data obtained from online questionnaire sent to 160 respondents – university students in the Special Region of Yogyakarta Indonesia, selected by using purposive sampling method. Data analysis is carried out using multiple regression. The research findings reveal that reputations and service features have a positive and significant influence on the intention to use e-wallet, while perceived risks and promotions do not influence the intention to use e-wallet. Furthermore, experiences do not influence of perceived risks, reputations, service features, and promotions on the intention to use e-wallet.